Influence ofGlaze Solution Mixed with Rosemary Oil on theOxidative Stability of Frozen Trout - Çoban, Özlem Emir; İnanlı, Gürel Ayşe (My University, 2018)
In this study, it was investigated that the influence of glaze solution mixed with rosemary oil on the oxidative stabilityof frozen trout. 1% and 5%rosemary oil solution were used for glazing. Water-glazed (WG) and nonglazed (NG) rainbow trout fillets were used as controlgroups.Fish filets frozen at -25°Cwere glazed and were stored in a freezer at -18°C for 6 months.Samples were analyzed monthly for total volatile basic nitrogen, thiobarbituric acid, peroxide value and free fatty acids. According to our results, rosemary oil was found effective in controlling lipid oxidation in frozen rainbow trout fillet (p< 0.05).
Keywords: Balıkçılık; Gıda Bilimi ve Teknolojisi